Factors Related to Greater Functional Recovery after Suffering a Stroke - María Vázquez-Guimaraens; José L. Caamaño-Ponte; Teresa Seoane-Pillado; Javier Cudeiro (Brain Sciences, 2021)
Background: In a stroke, the importance of initial functional status is fundamental for prognosis. The aim of the current study was to investigate functional status, assessed by the Functional Independence Measure (FIM) scale, and possible predictors of functional outcome at discharge from inpatient rehabilitation. Methods: This is a retrospective study that was carried out at the Physical Medicine and Rehabilitation Service in A Coruña (Spain). A total of 365 consecutive patients with primary diagnosis of stroke were enrolled. The functional assessments of all patients were performed through the FIM. A descriptive and a bivariate analysis of the variables included in the study was made and a succession of linear regression models was used to determine which variables were associated with the total FIM at discharge. Results: Prior to having the stroke, 76.7% were totally independent in activities of daily living. The FIM scale score was 52.5 ± 25.5 points at admission and 83.4 ± 26.3 at hospital discharge. The multivariate analysis showed that FIM scores on admission were the most important predictors of FIM outcomes. Conclusions: Our study indicates that the degree of independence prior to admission after suffering a stroke is the factor that will determine the functionality of patients at hospital discharge.